1998
DOI: 10.1192/bjp.173.3.249
|View full text |Cite
|
Sign up to set email alerts
|

Culturally sensitive validation of screening questionnaires for depression in older African– Caribbean people living in south London

Abstract: At a cut-off of > or = 4 the 15-item GDS can be recommended as a case detector for significant forms of depression in older African-Caribbean people living in south London.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 16 publications
1
35
0
Order By: Relevance
“…Hence, different cut-off values of the GDS have been used in various cultures. British studies utilised a cut-off of 4/5 (Shah et al, 1996), while studies on Africian-Caribbean people living in South London suggested an optimal cut-off of 3/4 (Abas et al, 1998). Variation in cut-off values also exists among Chinese in difference localities.…”
Section: Discussionmentioning
confidence: 93%
“…Hence, different cut-off values of the GDS have been used in various cultures. British studies utilised a cut-off of 4/5 (Shah et al, 1996), while studies on Africian-Caribbean people living in South London suggested an optimal cut-off of 3/4 (Abas et al, 1998). Variation in cut-off values also exists among Chinese in difference localities.…”
Section: Discussionmentioning
confidence: 93%
“…, 1997). When screening for depression in older When screening for depression in older people, lower cutpoints have been found people, lower cutpoints have been found to be appropriate for older Black people to be appropriate for older Black people living in the UK (Abas living in the UK (Abas et al et al, 1998). This , 1998).…”
Section: African^caribbeans African^caribbeansmentioning
confidence: 99%
“…Given the forthcoming expansion 1996). Given the forthcoming expansion of the older ethnic minority, information is of the older ethnic minority, information is required about their health needs (Abas required about their health needs (Abas et et al al, 1998;Acheson, 1998). There have been , 1998;Acheson, 1998).…”
mentioning
confidence: 99%
“…The CCSS was developed 'a priori' by ascertaining terminology used to describe emotional distress, 119 because older African Caribbeans rarely use the terms 'sad' or 'unhappy' to describe emotional distress, but they use other terms including 'being low spirited', 'fed up' and 'weighed down'. 117,119,120 In general, lower cutoff scores have been suggested on some scales like the GDS for African Caribbean older people in the UK. 117 The Symptoms of Anxiety and Depression Scale 121 was used as a diagnostic instrument for depression in Gujarati, Somali and Bengali older people in London, 28,31 but data on its psychometric properties are not available.…”
Section: Screening and Diagnostic Instrumentsmentioning
confidence: 98%
“…112,113 Orientation items of the MMSE, selected items of the CERAD battery and the clock drawing test have been evaluated also in older African Caribbeans in the UK. 114 Three depression screening instruments, including the 15-item Geriatric Depression Scale (GDS), 115 Brief Assessment Schedule Cards (BASDEC) 116 and Caribbean Culture Specific Screen (CCSS) 117 for use in African Caribbean older people in the UK were successfully evaluated against a 'gold standard' diagnosis of depression on the Geriatric Mental State Examination (GMS). 118 All three instruments showed satisfactory sensitivity and specificity in detecting depression in older Jamaicans with little difference between the three scales.…”
Section: Screening and Diagnostic Instrumentsmentioning
confidence: 99%